Treatment of Pathological Humerus-Shaft Tumoral Fractures with Rigid Static Interlocking Intramedullary Nail-22 Years of Experience - Moura, DL (2019)
Objective  This was a retrospective observational study in patients submitted to intramedullary nail fixation after established or impeding pathological humerus-shaft tumoral fracture in the context of disseminated tumoral disease along 22 years of experience at the same institution. Methods  Sample with 82 patients and 86 humeral fixations with unreamed rigid interlocking static intramedullary nail by the antegrade or retrograde approaches. Results  The most prevalent primary tumors were breast carcinoma (30.49%), multiple myeloma (24.39%), lung adenocarcinoma (8.54%), and renal cell carcinoma (6.10%). The average surgical time was 90.16 ± 42.98 minutes (40-135 minutes). All of the patients reported improvement in arm pain and the mean Musculoskeletal Tumor Society (MSTS) score rose from 26% in the preoperative period to 72.6% in the evaluation performed in patients still alive 3 months after the surgery. The overall survival was 69.50% 3 months after the surgery, 56.10% at 6 months, 26.70% at 1 year, and 11.90% at 2 years. No death was related to the surgery or its complications. There were only 4 surgery-related complications, 1 intraoperative and 3 late, corresponding to a 4.65% complication risk. Conclusion  Closed unreamed static interlocking intramedullary nailing (both in the antegrade or retrograde approaches) of the humerus is a fast, safe, effective, and low morbidity procedure to treat pathological fractures of the humerus shaft, assuring a stable arm fixation and consequently improving function and quality of life in these patients during their short life expectation.